'This is Possibly the Hardest Decision a Parent has to Make.' Deciding when your Child is Ready to Start Prep. Issue 2 (June 2017) - Mergler, Amanda; Walker, Sue
WHILE THE MAJORITY OF Queensland state school students begin schooling in the first year they are eligible to do so, a small number of families delay entry. This paper explores voluntary delayed entry to state schools in Queensland through analysis of quantitative data gathered by the Department of Education and Training, and parental decision making around delayed entry via qualitative data sourced from an Australian parenting website. Results revealed that the number of children who are delayed entry is increasing, and that the majority of students delayed are boys who are the youngest in their cohort. A key reason for parents choosing to delay is the child's birth date being close to the state's cut-off entry date. Importantly, the decision of whether to delay entry appears to be emotional for parents, and it is argued that parents require support and services to help them make this decision.